On the enigma of Palaenigma wrangeli (Schmidt), a conulariid with a partly non-mineralized skeleton - Björn Kröger; Olev Vinn; Ursula Toom; Ian J. Corfe; Jukka Kuva; Michał Zatoń (PeerJ, 2021)
Palaenigma wrangeli (Schmidt) is a finger-sized fossil with a tetraradiate conical skeleton; it occurs as a rare component in fossiliferous Upper Ordovician strata of the eastern Baltic Basin and is known exclusively from north Estonia. The systematic affinities and palaeoecology of P. wrangeli remained questionable. Here, the available specimens of P. wrangeli have been reexamined using scanning electron microscopy and x-ray computed tomography (microCT). Additionally, the elemental composition of the skeletal elements has been checked using energy dispersive X-ray spectroscopy. The resulting 2D-, and 3D-scans reveal that P. wrangeli consists of an alternation of distinct calcium phosphate (apatite) lamellae and originally organic-rich inter-layers. The lamellae form four semicircular marginal pillars, which are connected by irregularly spaced transverse diaphragms. Marginally, the diaphragms and pillar lamellae are not connected to each other and thus do not form a closed periderm structure. A non-mineralized or poorly mineralized external periderm existed originally in P. wrangeli but is only rarely and fragmentary preserved. P. wrangeli often co-occurs with conulariids in fossil-rich limestone with mudstone–wackestone lithologies. Based on the new data, P. wrangeli can be best interpreted as a poorly mineralized conulariinid from an original soft bottom habitat. Here the new conulariinid family Palaenigmaidae fam. nov. is proposed as the monotypic taxon for P. wrangeli.